As mothers of the land : the birth of the bougainville women for peace and freedom - Sirivi, Josephine Tankunani; Havini, Marilyn Taleo (Pandanus, 2004)
"The lights went out in Bougainville in 1990. In an attempt to force the island to give up its claims for independence, the government of Papua New Guinea imposed a military blockade, withdrawing all government and commercial services. The PNG military took control, imposed a permanent curfew and began an armed campaign against Bougainvillean rebel forces." "As Mothers of the Land is a unique account of one of the deadliest conflicts in recent decades, told not by military or political chiefs, but by those caught in the middle of the fighting: Bougainvillean women." "Bougainville is a matrilineal society, in which women are custodians of the land, but, as the conflict escalated, they became unwilling pawns in the fight to control the country's destiny. They were forced from their homes and herded into PNG-controlled 'care centres' or were forced to live on the run, fleeing to the jungle to escape violence, rape and military rule." "Normal society fractured as fear and anarchy took hold. With no access to health, education and basic community services, women were forced to call on traditional knowledge and self-reliance to rebuild a sense of community in the heart of the jungle. They also began to build a women's movement for peace and freedom." "As Mothers of the Land is a record of the years of war and the quest for peace, told by the women who lived through it. It is an essential record of the vital role women played in the Bougainville peace process and their remarkable achievements in a country torn apart by decades of violent struggle."--Jacket.